A invenção da Academia de Polícia Militar (1809-1958) - Loureiro, Samuel Robes (2017)
This thesis examines the ways in which the histories of the Military School of Realengo (EMR), the Military Police Academy of Barro Branco (APMBB) and the Officers’ Training School (EFO) of the Military Police of the Federal District (PMDF) are interwoven. The main objective was to uncover the process of the creation and consolidation of a particular military school model present throughout the country: Military Police Academies (APMs). The research sought to prove the hypothesis that the APM prototype would have resulted from a mixture of the curriculum of the professional course of the PMDF, created in 1920, and the traditions invented by the José Pessoa reform in the EMR, between 1931 and 1934, and also that the first school which underwent this transformation was the APMBB, between 1935 and 1938. From there, the model would have been disseminated to all Brazilian Military Police (PMs), including the PMDF itself. The research advances studies in the history of school institutions and educational intellectuals, with an emphasis on the processes of the invention of traditions, the reformulation of curricula, and the history of school subjects. Starting from a criticism of the theoretical-methodological reference of Althusserian structuralism, the work references ideas such as Thompson's notion of experience, Hobsbawm’s invention of tradition, and the meaning of the term intellectual as attributed by Sirinelli. This reference was supplemented by notions from Anthropology like Gilberto Velho's “field of possibilities” and Celso Castro's “military spirit”. Specific references from the history of education also provided support for the research, including notions of curriculum from Goodson, Forquin, Sacristan and Circe Bittencourt, as well as Cherval's ideas about the history of school subjects. As research involving the invention of traditions, the origins and the stabilization of these traditions were examined, which involved taking a historical cross-section covering the founding of the Military Division of the Royal Guard of Police in 1809 to the consolidation, in 1958, of the ceremony in which the cadets receive their swords in the EFO of the PMDF. For this purpose, an investigation of a variety of sources was necessary: personal archives, official documents, legislation, archives of materials, press, among others. It was possible to conclude that that the APMs were an invention of Brazilian army officers who adapted the traditions idealized for the EMR between 1931 and 1934 and the curriculum of the PMDF’s professional course from 1920. They created a new type of military school that was established in São Paulo at the APMBB between 1935 and 1938, and then disseminated throughout the country. The purpose of this invention would be to facilitate the transformation of state military forces into MPs, the army’s reserve and auxiliary force. However, such a standard was not imposed on state military forces, it was desired; and the companies not only assimilated but improved this new type of military school. As a result, state military forces became PMs, the army's reserve force, in order to survive the imminent threat of extinction after the Revolution of 1930 and the end of the governors' policies